Phytoplankton Diversity as a Bioindicator of Water Quality Mangrove Ecosystems in Clungup Mangrove Conservation, Kondang Merak and Sempu Island, Malang Regency - Satria Cahya Febriansyah; Luchman Hakim; Saptoyo Saptoyo; Catur Retnaningdyah (Universitas Gadjah Mada, 2023)
Local community groups have handled damage to the mangrove ecosystem on the coast of South Malang by carrying out restoration. The purpose of this study was to evaluate water quality in the restoration mangrove ecosystem based on phytoplankton diversity as bioindicators. A water and phytoplankton sampling was repeated three times with a depth of about 10-15 cm (below the surface water) at each location consisting of 4 restored mangrove ecosystems in Clungup Mangrove Conservation (CMC) and Kondang Merak as well as one natural mangrove ecosystem in Teluk Semut, Sempu Island, Malang Regency. Water quality parameters include water temperature, air temperature, conductivity, pH, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), nitrate, and orthophosphate content. The biotic index includes the Trophic Diatom Index (TDI) as an indicator of water nutrient content and Percentage Pollution Tolerance Value (%PTV) as an indicator of organic pollution. The water quality in the five mangrove ecosystems of CMC, Kondang Merak, and Teluk Semut has met the water quality standard for marine biota except for DO, nitrate, and orthophosphate content in several locations. Water quality in five mangrove ecosystems CMC, Kondang Merak, and Teluk Semut based on phytoplankton indicators did not show any contamination with toxic materials (H’). Based on TDI, it is categorized as eutrophic – hypereutrophic, except at the reference site of Teluk Semut mangrove; based on PTV polluted with moderate to high organic matter except at the reference site locations, namely Teluk Semut, and CMC 2. Thus, a location that has good phytoplankton bioindicators is Teluk Semut.